Abnormalities of lipid metabolism in the progression and treatment of depression - Luan, Xinchi; Wang, Xuezhe; Shi, Ying; Zhang, Xinyi; Wang, Yilin; Zhou, Miao; Wu, Zhaoyi; Liu, Zijiao; Li, Xiaoxuan; Zhang, Lihua; Shao, Tianyi; Chen, Ruolan; et al. (Frontiers in Psychiatry, 2025)
Depression represents a global health challenge with complex etiology and significant societal impact. Recent advancements reveal a critical role of lipid metabolism dysregulation in the pathogenesis and severity of depressive disorders. This review elucidates the impact of lipid imbalance on depression highlighting how dyslipidemia not only makes individuals prone to depression but also exacerbates the progression of depression (including the occurrence of some comorbidities of depression). On this basis, we have summarized that abnormal lipid metabolism may serve as a diagnostic and therapeutic target for depression. We discuss the perturbation of lipid homeostasis in depression, marked by altered triglycerides and high-density lipoprotein levels, and the potential of these lipids as biomarkers for diagnostic precision and therapeutic efficacy. Special emphasis is placed on the molecular mechanisms where lipids influence neuronal function and stress responses, thereby affecting mood and cognitive outcomes. Furthermore, we explore the comorbidity of depression with other systemic illnesses, suggesting a shared lipid-mediated metabolic pathway. Given the integral role of lipids in neural architecture and signaling, targeting lipid metabolism could offer novel therapeutic avenues, enhancing neuroplasticity and potentially mitigating depressive symptoms. Our synthesis aims to pave the way for future investigations into lipid-centric strategies to combat depression, advocating for a metabolic reorientation in mental health therapeutics.